The Emotion of Interest and its Relevance to Consumer Psychology and Behaviour - Sung, Billy; Phau, Ian; Vanman, E.; Hartley, N. (Elsevier, 2016)
Consumers are known to show a paradoxical tendency to favour both familiar and novel marketing stimuli such as products and advertisements. However, an explanation for this paradox has yet to be proposed. This provides immense challenges for marketing practices that conventionally strive to build familiarity (e.g. building awareness, recognition, recall, and customer relationships). Using the emotion differentiation framework, this theoretical paper shows that this paradox is a result of two distinct emotions – liking and interest. Specifically, consumers like familiarity but are interested in novelty. This paper offers six empirical propositions to: (1) differentiate interest from liking; (2) show that liking motivates consumers to favour familiarity whereas interest motivates consumers to prefer novelty; (3) demonstrate that interest accounts for previously explained boundary conditions of the familiarity–liking effect; and (4) provide insights to explain previous conflicting findings in the field of innovation, advertising, and consumer psychology research.